The effect of composition, annealing temperature and thickness on magnetoresistance of ferromagnetic multilayer structures - Nazimah Khamis @ Subari, 1974-; Yussof Wahab, supervisor; Samsudi Sakrani, supervisor; Fakulti Sains (2010)
Thesis (Sarjana Sains (Fizik)) - Universiti Teknologi Malaysia, 2010